Analisis Perkembangan Kedudukan Perempuan dalam Pewarisan Hukum Adat Batak Toba di Kota Malang - Lumban Gaol, Sastra Gunawan; Budiastanti, Dhaniar Eka; Shanty, Wika Yudha; Ariyanti, Ariyanti; Mulyono, Galih Puji (University of Merdeka Malang, 2024)
The Indonesian nation has a wealth of customs which form a strong identity in the lives of its people. One custom that has its own characteristics is the Toba Batak tradition, especially in terms of dividing inheritance. In the Toba Batak traditional inheritance system, the distribution of inheritance traditionally prioritizes sons. This is different from the provisions in the Indonesian Civil Code (KUHPerdata) which equalize inheritance rights between sons and daughters. This research uses empirical legal research methods which aim to examine the position of girls in Toba Batak traditional inheritance law in Malang City, as well as to identify factors that influence changes in perspectives on girls' inheritance rights. Apart from that, this research also seeks to understand the mechanism for resolving traditional inheritance disputes carried out by Toba Batak traditional leaders. The research results show that although the Toba Batak community in Malang City still adheres to a patrilineal system, there has been significant development in recognizing the inheritance rights of girls. Girls are now starting to get equal inheritance rights with boys, especially for property obtained from their own hard work. Efforts to resolve traditional inheritance disputes by Toba Batak traditional leaders in Malang City also show an effort to bridge traditional values with modern realities, creating harmony between customary law and state law.